On Some Problems of the Asymptotic Theory of Linear Differential Equations of the nth Order - Evtukhov, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We investigate smoothness properties of the roots of algebraic equations with almost constant coefficients and construct a transformation, which may be efficiently used for the investigation of the asymptotic behavior of a fundamental family of solutions of a broad class of nonautonomous linear differential equations of the nth order.